The issue of freedom and engaged literature - Prado, Lucas do (2023)
In this study, we will try to briefly reconstruct the interpretation of literature for Jean-Paul Aymard Sartre, described in the book Qu’est ce que la littérature? (What is literature?). For this to be possible, we will try to understand the construction of Sartre's idea about literature and how the writer and his work are related and depend on their audience and the act of reading, that is, why this relationship between writer and reader is of fundamental importance in Sartre's conception for the construction of literature. After understanding the construction made by Sartre, between writer and reader, we will try to find out some points of his semantic interpretation of literature made at the time of his writing, the 20th century. We will seek to analyze whether the exegesis of the text still has thematic contributions that we can still use up to the present moment, or if Sartre's explanation remains as a relic of the past or a literary star in eclipse